Polymorphism of the dopamine D4 receptor (DRD4) and serotonin transporter (5-HTTL) gene promoter regions in african tribes of Hadza and Datoga - Vasilyev, V. A; Martirosyan, I. A; Shibaev, D. V; Kulikov, A. M; Lazebny, O. E; Burkova, V. N; Ryskov, A. P; Butovskaya, M. L (Russian journal of genetics, 2011)
Molecular genetic analysis of the allelic variants of the DRD4 and 5-HTTL gene promoter regions was performed in African tribes of Hadza and Datoga, characterized by different levels of socially acceptable aggression. It was demonstrated that Hadza and Datoga people differed in the structural organization of one of the 5-HTTL alleles (extra long allele xL). Analysis of the allele length polymorphism of both genes showed that in the Hadza and Datoga samples examined, variation parameters, as well as the genotype and allele frequency distribution pattern were almost the same. At the same time, analysis of the SNP polymorphism at the A/G substitutions of the 5-HTTL locus revealed a substantial decrease of the active allele L A frequency in the population of Hadza compared to the population of Datoga (χ² = 3.77; d.f. = 1; p = 0.052).